Challenges to Performance Management in Health Care Entities During Crisis Situations - Chluska, Jolanta (Journal of Public Governance, 2023)
Objectives: The article aims to identify the challenges faced by the management of health care entities – clinical hospitals – in evaluating their performance during crises. The research hypothesis posits that crises add new areas to the performance evaluation of health care entities – clinical hospitals – and alter their evaluation tools.Research Design & Methods: The research was empirical, based on the reporting data for the period 2019–2021 (quantitative and qualitative) in selected clinical hospitals. The analyses were performed by an expert and included the perspective of a certified auditor and long-term researcher of issues related to the operation of health care entities – hospitals.Findings: Health care entities in Poland, as public sector entities, incorporate crisis management requirements into their activities.Implications / Recommendations: The results of the analyses are addressed mainly to the constituent bodies of health care entities, institutions affecting the operation of the health care system, and hospital managers.Contribution / Value Added: It has been shown that crises add new areas to the performance evaluation of health care entities – clinical hospitals – and alter their evaluation tools.Article Classification: research articleJEL classification: M40, M41, L21